Ultrasound-assisted activation of zero-valent magnesium for nitrate denitrification: Identification of reaction by-products and pathways - Ileri, Burcu; Ayyildiz, Onder; Apaydin, Omer (ELSEVIER SCIENCE BV, 2015)
Zero-valent magnesium (Mg-0) was activated by ultrasound (US) in an aim to promote its potential use in water treatment without pH control. In this context, nitrate reduction was studied at batch conditions using various doses of magnesium powder and ultrasound power. While neither ultrasound nor zero-valent magnesium alone was effective for reducing nitrate in water, their combination removed up to 90% of 50 mg/L NO3-N within 60 min. The rate of nitrate reduction by US/Mg-0 enhanced with increasing ultrasonic power and magnesium dose. Nitrogen gas (N-2) and nitrite (NO2-) were detected as the major reduction by-products, while magnesium hydroxide Mg(OH)(2) and hydroxide ions (OH-) were identified as the main oxidation products. The results from SEM-EDS measurements revealed that the surface oxide level decreased significantly when the samples of Mg particles were exposed to ultrasonic treatment. The surface passivation of magnesium particles was successfully minimized by mechanical forces of ultrasound, which in turn paved the way to sustain the catalyst activity toward nitrate reduction. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ultrasound; Zero-valent magnesium; Nitrate; Denitrification; Surface activation; ACID ORANGE 7; CHEMICAL-REDUCTION; AQUEOUS-SOLUTION; IRON; REMOVAL; DECHLORINATION; DEGRADATION; WATER; DYE; Engineering; Environmental Sciences & Ecology